Applying big data analytics in bioinformatics and medicine - Lytras, Miltiadis D., 1973-; Papadopoulou, Paraskevi, 1961- (Advances in bioinformatics and biomedical engineering book series., 2018)
"This book explores the latest developments in Bioinformatics and Health Informatics but to also put emphasis on increasing awareness of all stakeholders of the importance to move from a data management organizational culture to a learning organization culture. It explores the biological relevance of genomic and proteomic discoveries and related specific gene expression to achieve targeted therapy"--Provided by publisher.